Assessment of Marinas in the Mediterranean and the Position of Turkey - Pinar Genc, Evrim; Guler, Nil (Promet - Traffic&Transportation, 2006)
The most important organizations for developing and advertisingthe yacht tourism in a country are the marinas.Yachting tourism, being a part of maritime sector tends to playa part in the tourist activities and provides important resourcesfor the general economy.In this study, the developments in yachting tourism are aplainedby considering the cu'ent status of the marinas in theMedite'anean countries. Basic characteristics of different marinasof the Medite'anean countries will be discussed and alsostatistical figures will be given. The yachting routes and the potentialof Turkey will be analyzed by emphasizing operational,infrastructural and service characteristics. The factors thatshould be taken into consideration and the methods used formarina marketing will be explained. By considering strengths,weaknesses, opportunities and threats, a SWOT analysis will bemade for Turkey marinas. Suggestions will be given fur furtherdevelopment of marina management in Turkey.